Pembelajaran IPA Berbasis Problem Based Learning Ditinjau dari Keterampilan Proses Sains Siswa - Abidin, Zainal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The purpose of this research is to determine differences in student learning outcomes based on science process skills with the problem based learning model seen from student learning outcomes at Keruak 1 Middle School, East Lombok Regency. This type of research is quasi-experimental, taking samples using purposive sampling. The sample for this research was 43 male students from class VIII. Data collection techniques in this research used observation, documentation and tests. The research instrument used questionnaires and written tests. The results of this research include: 1) science learning using a problem based learning model based on science process skills makes teaching and learning activities more enjoyable; 2) the highest category of student learning outcomes is found in the skills aspect; and 3) students can develop their potential to be more active in learning about the respiratory system material. The problem based learning model is able to provide opportunities for students to be able to solve a problem in a project through real experience. However, there are still some aspects that are low, such as the attitude aspect, where students are just getting to know this learning model. More varied learning will be useful in improving students' skills through problem based learning models based on science process skills or other learning models according to the subject matter.